2007
DOI: 10.1073/pnas.0701519104
|View full text |Cite
|
Sign up to set email alerts
|

Network structure of cerebral cortex shapes functional connectivity on multiple time scales

Abstract: Neuronal dynamics unfolding within the cerebral cortex exhibit complex spatial and temporal patterns even in the absence of external input. Here we use a computational approach in an attempt to relate these features of spontaneous cortical dynamics to the underlying anatomical connectivity. Simulating nonlinear neuronal dynamics on a network that captures the large-scale interregional connections of macaque neocortex, and applying information theoretic measures to identify functional networks, we find structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

90
1,388
8
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,631 publications
(1,487 citation statements)
references
References 52 publications
90
1,388
8
1
Order By: Relevance
“…(Friston, 1997(Friston, , 2000), computational (e.g. (Breakspear et al, 2003, Honey et al, 2007, Ghosh et al, 2008, Deco et al, 2009 (Brookes et al, 2012b). Indeed this finding has been mirrored by other MEG studies (Hipp et al, 2012), and is in general agreement with findings from simultaneous electroencephalography (EEG) / fMRI.…”
Section: ) Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…(Friston, 1997(Friston, , 2000), computational (e.g. (Breakspear et al, 2003, Honey et al, 2007, Ghosh et al, 2008, Deco et al, 2009 (Brookes et al, 2012b). Indeed this finding has been mirrored by other MEG studies (Hipp et al, 2012), and is in general agreement with findings from simultaneous electroencephalography (EEG) / fMRI.…”
Section: ) Introductionsupporting
confidence: 85%
“…(Friston, 1997(Friston, , 2000), computational (e.g. (Breakspear et al, 2003, Honey et al, 2007, Ghosh et al, 2008, Deco et al, 2009) and empirical (e.g. (Breakspear et al, 2004, Bassett et al, 2006) evidence suggests that complex and highly temporally variable neuronal dynamics underlie the coupling observed between spatially separate brain regions.…”
Section: ) Introductionmentioning
confidence: 99%
“…The idea is to infer structural connectivity from DWI data and use it as an additional constraint in our Bayesian model. The validity of this approach is supported by several recent experimental studies which found a substantial overlap between structural and functional networks both inside specific cortical areas (Koch et al, 2002) and on a whole brain scale (Hagmann et al, 2008;Honey et al, 2009Honey et al, , 2007Damoiseaux and Greicius, 2009;Greicius et al, 2009;Cabral et al, 2012). Related approaches have been used before in the context of functional and effective connectivity analysis (Stephan et al, 2009;Deligianni et al, 2011;Ng et al, 2012).…”
Section: Introductionmentioning
confidence: 83%
“…Their anatomical locations, as well as the extent to which the matrix covers the surface of macaque cortex are shown in the panels at the top of the figure (lateral and medial views, respectively). Blue and green represents cortices belonging to the two major clusters identified by spectral methods (Honey et al, 2007). (B) Proportions of the total DSI fiber mass that are coinciding with "known present," "unknown," and "known absent" Cocomac pathways.…”
Section: Validation Of Mr Tractography and Connectivity Mapsmentioning
confidence: 99%
“…Towards this objective, a number of computational studies have attempted to combine interregional connectivity data with intra-regional circuit and cellular properties to produce large-scale models of cortical (Ghosh et al, 2008;Honey et al, 2007Honey et al, , 2009Knock et al, 2009) and corticothalamic function (Izhikevich and Edelman, 2008). The value of modeling studies is twofold.…”
Section: Functional Connectomicsmentioning
confidence: 99%